3) idk how to answer that... If its a true or false question true
12) um... That one's kind of confusing but my best guess is somewhere in the 3rd quadrant
7 can go into 97 13 times w/ a remainder of 6.
Let the numbers be x and y, then
2x + y = 47 . . . (1)
x + 3y = 56 . . . (2)
(2) x 2 => 2x + 6y = 112 . . . (3)
(1) - (3) => -5y = -65 => y = -65/-5 = 13
From (2), x + 3(13) = 56 => x = 56 - 39 = 17
The two numbers are 13 and 17.
If we observe the graph we can see that the curve crosses the x-axis at the following points: 1, 3, and 5
This means x = 1, x = 3 and x = 5 are the roots of the polynomial and x - 1, x - 3 and x - 5 are the factors of the polynomial.
We can express the polynomial as the product of its factors. So the polynomial will be (x-1)(x-3)(x-5)
The correct answer to this question is option A
Answer:
Given that rotating 90 degrees clockwise around the origin switches the x andy values and makes the new y value negative, we can, for example, switch (2, 1) to (1, -2). 180 degrees clockwise simply makes both values negative (-2, -1), and 270 degrees clockwise switches them and makes the new y value negative (-1, 2), we can plug those in to our JM endpoints to turn (-5, 1) into (-1, -5) and (-6, 2) into (-2, -6)
Step-by-step explanation: